2021
DOI: 10.3906/bot-2106-8
|View full text |Cite
|
Sign up to set email alerts
|

Ecological assessment of Burç Reservoir’s surface water (Turkey) using phytoplankton metrics and multivariate approach

Abuzer ÇELEKLİ,
Gülümser ÖZPINAR

Abstract: The present study was aimed to elucidate relationships between phytoplankton species and stressors using multivariate approaches and assess the environmental condition of Burç Reservoir's surface water using phytoplankton metrics from September 2018 to August 2019 according to implementations of the Water Framework Directive. Burç Reservoir had a characteristic of a warm monomictic pattern. Phytoplankton functional groups (E, F, J, L O , L M , MP, P, S1, T, and W1) were found in the reservoir. A significant di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…The MPTI had a higher correlation coefficient value than the Med‐PTI in the Antalya River basin due to variations in their approaches. The PTI was reported previously in 1795 lakes in 20 European countries (Phillips et al., 2013), 12 lentic ecosystems of Western Mediterranean basin (Çelekli & Lekesiz, 2021), 32 lakes in 11 European countries (Thackeray et al., 2013), various lakes in the Aras River basin (Çelekli et al., 2020), 313 Swedish lakes (Zhao et al., 2019), and Burç Reservoir in the southeast Anatolia (Çelekli & Özpınar, 2021).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The MPTI had a higher correlation coefficient value than the Med‐PTI in the Antalya River basin due to variations in their approaches. The PTI was reported previously in 1795 lakes in 20 European countries (Phillips et al., 2013), 12 lentic ecosystems of Western Mediterranean basin (Çelekli & Lekesiz, 2021), 32 lakes in 11 European countries (Thackeray et al., 2013), various lakes in the Aras River basin (Çelekli et al., 2020), 313 Swedish lakes (Zhao et al., 2019), and Burç Reservoir in the southeast Anatolia (Çelekli & Özpınar, 2021).…”
Section: Discussionsupporting
confidence: 51%
“…The health of aquatic ecosystems can be assessed by estimating phytoplankton number and structure (Çelekli & Lekesiz, 2021;Zhu et al, 2021). Studies have been conducted in Anatolia on the phyto-assessment of lentic ecosystems and the interpretation of interactions between stressors and phytoplankton (Çelekli & Özpınar, 2021;Sevindik et al, 2017), but these studies have not been conducted at the river basin scale except by Toudjani et al (2018) and (Çelekli & Lekesiz, 2021). They used phytoplankton assemblages to evaluate the various aquatic ecosystems (brackish and freshwater lakes and reservoirs) in the Western Mediterranean basin, Turkey (Çelekli & Lekesiz, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of U. ulna and U. biceps in sample ST3 is notable, since U. ulna is recognized as highly resistant and tolerant to water pollution (Celekli and Öztürk, 2014;Dalu et al, 2015;Noga et al, 2016). On the other hand, U. biceps was retrieved in waters with high electrical conductivity (Celekli and ÖZPINAR, 2021) and phosphate concentration (Celekli and Öztürk, 2014). A series of experiments on diatom sensitivity to herbicides showed that U. ulna and U. biceps are resistant to high atrazine concentrations (Chakandinakira et al, 2019).…”
Section: Diatom Population As Ecological Indicator Of Pollutionmentioning
confidence: 96%